EXPERIMENTAL STUDY OF THERMOELECTRIC AIR DUCT AND PHOTOVOLTAIC SYSTEM FOR ENERGY EFFICIENT BUILDING DEVELOPMENT - IRSHAD, KASHIF (2016)
At present, effort of maintaining thermal comfort inside the buildings has become a great challenge faced by the majority of the developing countries. As the process of air conditioning, particularly in large buildings can lead to excessive use of energy. In this research, the performance of the test room were investigated in term of thermal load, thermal comfort, and energy by integrating three different systems comprise grid connected thermoelectric air duct (TE-AD) cooling system, south facing photovoltaic wall (PV-W) system, and PV assisted TE-AD cooling system for tropical climate at Perak, Malaysia. Firstly, a simulation model of the grid and PV assisted TE-AD system was developed by using TRNSYS software. Result shows that the temperature difference between experimental and simulation data were less than ±0.9°C.